Upholding confidentiality in the preparation and distribution of medication in prisons: implementing recommendations of the European Committee for the Prevention of Torture and Inhuman or Degrading Treatment or Punishment [version 1; peer review: 2 approved] - Hans Wolff; Nguyen Toan Tran (F1000Research, 2020)
Confidentiality must be ensured even in the preparation and distribution of medications in detention settings. In this respect, the European Committee for the Prevention of Torture and Inhuman or Degrading Treatment or Punishment found during recent prison visits several instances where prison staff, and at times detainees, dispensed prescribed treatments and supervised their intake. Such a practice compromises medical confidentiality requirements and the establishment of a trusting doctor-patient relationship. To respect medical confidentiality and ensure safety and quality of care, the authors argue that only qualified healthcare personnel should prepare and distribute prescribed medications, all of which require specialized training. They call for robust research that examines the operational barriers and facilitators as well as the respect of human rights related to various approaches to medication preparation, distribution, and intake so that people in detention can access their treatment with safety, confidentiality, autonomy, and dignity.